Predictors of pneumonia in lower respiratory tract infections: 3C prospective cough complication cohort study. Issue 5 (23rd November 2017) - Moore, Michael; Stuart, Beth; Little, Paul; Smith, Sue; Thompson, Matthew J.; Knox, Kyle; van den Bruel, Anne; Lown, Mark; Mant, David
The aim was to aid diagnosis of pneumonia in those presenting with lower respiratory tract symptoms in routine primary care. A cohort of 28 883 adult patients with acute cough attributed to lower respiratory tract infections (LRTIs) was recruited from 5222 UK practices in 2009–13. Symptoms, signs and treatment were recorded at presentation and subsequent events followed-up for 30 days by chart review. The predictive value of patient characteristics, presenting symptoms and clinical findings for the diagnosis of pneumonia in the first 7 days was established. Of the 720 out of 28 883 (2.5.%) radiographed within 1 week of the index consultation, 115 (16.0%; 0.40% of 28 883) were assigned a definite or probable pneumonia diagnosis. The significant independent predictors of radiograph-confirmed pneumonia were temperature >37.8°C (RR 2.6; 95% CI 1.5–4.8), crackles on auscultation (RR 1.8; 1.1–3.0), oxygen saturation <95% (RR 1.7; 1.0–3.1) and pulse >100·min –1 (RR 1.9; 1.1–3.2). Most patients with pneumonia (99/115, 86.1%) exhibited at least one of these four clinical signs; the positive predictive value of having at least one of these signs was 20.2% (95% CI 17.3–23.1). In routine practice, radiograph-confirmed pneumonia as a short-term complication of LRTI is very uncommon (one in 270). Pulse oximetry may aid the diagnosis of pneumonia in this setting. Pulse oximetry probably has a role in the diagnosis of pneumonia in the community http://ow.ly/QpWc30fVM2j